Preferences of eligible women from an Indian medical college hospital for adapting contraceptives - Gadre, Sandhya; Gadre, Abhishek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Indian women prefer to avoid unwanted pregnancy, but do not practice contraception adequately. After completing their family size, they are more concerned about terminating their fertility, rather than spacing the births. The main aim and objective of the study is to find out preferences for (a) Regularity if any, of barrier contraceptive usage (b) Use of any contraception at zero gravidity (c) The prevalence of temporary & permanent contraception (d) Prior practice of any temporary contraception before opting for tubectomy (e) Acceptance of male sterilization. Methods: The study was conducted at Obstetrics & Gynaecology department, Chirayu Medical College and Hospital, Bhopal, India. Women in reproductive age group, whether tubectomized or not & postmenopausal women, attending OPD, admitted or those working at the hospital were included. They were given a prestructured, pretested questionnaire. Sociodemographic details, reproductive & contraception details recorded. Analyzed as per the demands of the study objectives. Results: From total 267 study subjects, 81 % were practicing contraception. 103 temporary and 113 had sterilization done. Only 42 % were using barrier contraceptive effectively.46% of the temporary contraceptive users discontinued. There was no significant difference between temporary and permanent method users. 97% did not use any contraception at zero gravidity. 69% of the sterilized population never used any contraception before they underwent sterilization. There was only one vasectomy in 267 study subjects. Conclusions: The contraceptive methods are poorly practiced. The users do not use any temporary contraception effectively & adequately. A negligible percentage of eligible women practice contraception before first pregnancy. Very few women practice temporary methods any time before they get sterilization done. Overall, the concept of spacing is lacking. Women are more inclined towards permanent methods. Male sterilization is very rarely chosen by the couples.